The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf02011307
|View full text |Cite
|
Sign up to set email alerts
|

The plain abdominal film in intussusception: The accuracy and incidence of radiographic signs

Abstract: The incidence of four plain abdominal film features associated with intussusception was recorded by four observers in 180 films of patients with intussusception mixed with 100 films of control subjects. The crescent sign and target sign were the most accurate indicators of intussusception. The target sign was the commoner being seen in 68% of films. Signs of small bowel obstruction were not useful in the diagnosis of intussusception. The soft tissue mass was the commonest indicator of intussusception. The soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…25,26,38,40 In the present study, a highly suggestive abdominal radiograph was found to be an important independent predictor. Intussusception, however, also occurred in 21% of patients without highly suggestive radiographs, similar to what has been reported previously.…”
Section: Commentmentioning
confidence: 63%
See 2 more Smart Citations
“…25,26,38,40 In the present study, a highly suggestive abdominal radiograph was found to be an important independent predictor. Intussusception, however, also occurred in 21% of patients without highly suggestive radiographs, similar to what has been reported previously.…”
Section: Commentmentioning
confidence: 63%
“…The utility of plain radiographs in diagnosing intussusception has been the subject of controversy, with regard to their sensitivity and specificity 2,[24][25][26][36][37][38][39][40][41] as well as to interobserver reliability. 25,26,38,40 In the present study, a highly suggestive abdominal radiograph was found to be an important independent predictor.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible features include soft tissue mass, target sign, or meniscus sign. 17 The first-line investigation for diagnosis of intussusception in children is abdominal ultrasound, given its high sensitivity (98%-100%) and specificity (88%-100%). 18 Non-operative reduction methods for intussusception include barium enema, and hydrostatic or pneumatic reduction.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…Another commonly described plain radiograph finding is "target sign" [3] which consists of two concentric circles of fat density to the right of the spine in infants and children. The target sign is described to be twice as frequent as that of the crescent sign.…”
Section: Discussionmentioning
confidence: 99%